Normally-Off Hybrid Al2O3/GaN MOSFET on Silicon Substrate Based on Wet-Etching - Wang, Maojun; Wang, Ye; Zhang, Chuan; Wen, Cheng P.; Wang, Jinyan; Hao, Yilong; Wu, Wengang; Shen, Bo; Chen, Kevin J. (2014 IEEE 26TH INTERNATIONAL SYMPOSIUM ON POWER SEMICONDUCTOR DEVICES & IC'S (ISPSD), 2014)
This paper reports a normally-off high voltage hybrid Al203/GaN gate-recessed MOSFET fabricated on silicon substrate. The normally off operation was implemented by digital gate recess using an oxidation and wet etching based AlGaN barrier remove technique. The Al203/GaN MOSFET features a true normally off operation with a threshold voltage of 2 V extracted by the linear extrapolation of the transfer curve. The three terminal off-state breakdown voltage is 1650 V for the device with 30 gm gate-drain distance with floating Si substrate. The breakdown voltage is limited to 1000 V when the Si substrate is grounded. The on-resistance is 7.0 m Omega cm(2) for the device with 30 gm gate-drain distance and the power figure of merit is 388 MW/cm2. The small signal RF performance of the normally-off GaN MOSFET is also evaluated.